Q. 1

# If A + B + C = π, prove that

sin 2A + sin 2B – sin 2C = 4cos A cos B sin C

Answer :

= sin 2A + sin 2B – sin 2C

= 2 sin ( B + C ) cos A + 2 sin ( A + C ) cos B - 2 sin ( A + B ) cos C

using formula,

sin (A + B) = sin A cos B + cos A sin B

= sin 2A + sin 2B - sin 2C

Using formula

sin2A = 2sinAcosA

= 2sinAcosA + 2sinBcosB - 2sinCcosC

since A + B + C = π

And sin(π – A) = sinA

= 2sin(B + C)cos A + 2sin(A + C)cosB - 2sin(A + B)cosC

= 2 ( sin B cos C + cos B sin C ) cos A + 2(sinAcosC + cosAsinC)cosB - 2(sinAcosB + cosAsinB )cosC

= 2cosAsinBcosC + 2cosAcosBsinC + 2sinAcosBcosC + 2cosAcosBsinC– 2sinAcosBcosC – 2cosAsinBcosC

= 2cosAcosBsinC + 2cosAcosBsinC

= 4cosAcosBsinC

= R.H.S

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Conditional Identities31 mins

Incentre | Mastering important conceptsFREE Class

Orthocentre and escribed circles48 mins

Circumcentre & its properties54 mins

Solution of Triangles | Test Yourself | QuizFREE Class

Importance of Sine rule and cosine rule47 mins

Quiz on sine rule, cosine rule and half angle formula54 mins

Stewart's Theorem46 mins

Interactive Quiz on Half angle formula, circumcircle and incircle48 mins

Centroid | Mastering important conceptsFREE Class

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

If A + B + C = π, prove that

cos 2A – cos 2B + cos 2C = 1 – 4sin A cos B sin C

RS Aggarwal - Mathematics

If A + B + C = π, prove that

RS Aggarwal - Mathematics